2016
DOI: 10.1007/s10457-016-9948-5
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing biomass and carbon storage potential of different land use systems along an elevational gradient in temperate northwestern Himalaya

Abstract: We observed the influence of five different altitudes and prevailing agro ecosystems on biomass and carbon sequestration potential in Kullu district of Himachal Pradesh, India. The study area had five prevailing land uses viz., agriculture, agro-horticulture, horticulture, silvi-pasture, and forest at four elevations representing about 1°C temperature change. The results showed that maximum total biomass of 404.35 Mg C ha-1 was accumulated by forest landuse and followed a decreasing trend in the order as fores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(31 citation statements)
references
References 18 publications
(18 reference statements)
4
17
1
Order By: Relevance
“…In the present study, increase in biomass with increasing altitude has got support from reported literature of Zhao et al (2014), Zhu et al (2010), Rajput et al (2015) and Rajput et al (2017). The above variation in the biomass level at different altitudes can be explained on the basis of combined effect of age of woody species, soil organic carbon (%) and human population density.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…In the present study, increase in biomass with increasing altitude has got support from reported literature of Zhao et al (2014), Zhu et al (2010), Rajput et al (2015) and Rajput et al (2017). The above variation in the biomass level at different altitudes can be explained on the basis of combined effect of age of woody species, soil organic carbon (%) and human population density.…”
Section: Discussionsupporting
confidence: 86%
“…setegerus. The results of the present study indicate that total biomass production is influenced by the old age tree layer, herbaceous nature of plants, nature and number of woody components and is supported by the findings of Rajput et al (2015Rajput et al ( , 2017.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations